(untitled) (Research, Society and Development, 2021)
The species Copaifera martii (Hayne) is of great importance in folk medicine, since the oil extracted from the plant contains active principles that serve as a basis for the production of medicines. In this sense, the main objective of this work was to evaluate the phenological behavior (flowering, fruiting, leaf drop and budding) of Copaifera martii (Hayne) in a secondary forest area and to correlate with climatic data (precipitation, temperature, total insolation and relative humidity) and analyze the significance of these phenological events through the Spearman Correlation Coefficient Test (rs), Correlation Matrix and multiple linear regression analysis, this monitoring was carried out weekly during the period of three years (2018 to 2020 ). In this research, it was possible to register that defoliation occurred with greater force in the months (June to October), a period of lesser rainfall in the region. In the aspects of the temperature data in the same period, it was found that high temperatures and total insolation point to greater defoliation in the studied trees. With regard to the budding phenophase in relation to the abiotic precipitation agent, it is observed that the budding percentage followed the period of high rainfall, in the three periods comprising the months of January to May (2018, 2019 and 2020). Regarding the statistical test of Spearman correlation (rs), it revealed that there was no positive relationship between precipitation and relative humidity in the period evaluated for the “leaf fall” phenophase, since none of the results with this variable showed if significant. However, this phenophase was positive and significant in relation to the abiotic factor temperature and total insolation, registering a correlation of (rs) = 0.5860 and (rs) = 0.709 respectively. The variable “budding” was also positive and highly significant for the abiotic factors precipitation and relative humidity, registering a correlation coefficient of (rs)=0.838 and (rs)=0.871 respectively. Through the analysis of the correlation matrix regarding the leaf fall phenology, the data showed a positive correlation of 0.762 in relation to the abiotic factor total insolation and 0.657 for the temperature variable. The budding phenophase had a high positive correlation with precipitation and relative humidity, recording the values ​​of 0.805 and 0.888 respectively.